Sintesis Biopelumas Dari Minyak Biji Karet : Pengaruh Rasio Molar Antara Etilen Glikol Dan Asam Lemak Serta Waktu Reaksi Esterifikasi Terhadap Yield Biopelumas - Fenny Lasma Hilde S; Irdoni Irdoni; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Lubricants used to protect engine components from worn-out. Rubber seed oil is an oil that can not be consumed cause toxicthus potentially used as raw material for biolubricants. This research purposes to study the synthesis of biolubricants from rubber seed oil to observe the effect of rasio mol between fatty acid and time of esterification reaction to the yield of the product. The research was begun with the extraction of rubber seed to get the oil. Then, the oil was degumming to purify the oil from the gum. Next, the oil was hydrolysis to make fatty acid and glycerol. Furthermore, fatty acids will be esterified with etylen glycol on a mole ratio of 3:1, 6:1 and 9:1, and time reaction for 2,3 and 4 hours, stirring speed 180 rpm, and the reaction temperature is 150 oC. The yield raised with the increase of fatty acid rasio mol and time of reaction. The highest yield is 79,772 % at 4 hours time of reaction with 9:1 rasio mol fatty acid and etylene glycol at stirring speed of 180 rpm. Flash point of the biolubricant is 387°C, pour point 7°C, density 0,9143 g/ml and viscosity index amounted 162,329.Keywords: biolubricants, esterification, etylen glycol, rubber seed oil, yield